2010
DOI: 10.1007/s10103-010-0781-1
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effect of photodynamic therapy using a highly pure chlorin e6

Abstract: The aim of the present study is to evaluate the antimicrobial effect of photodynamic therapy (PDT) using a highly pure chlorin e(6) (Ce(6)), against various pathogenic bacteria. To examine the antimicrobial effect of Ce(6)-mediated PDT against Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, and Salmonella enterica serovar Typhimurium, inhibition zone formation, CFU quantification, and bacterial viability were evaluated. Inhibition zone analysis showed that Ce(6)-mediated PDT is very effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 19 publications
1
49
1
4
Order By: Relevance
“…In previous studies with porphyrinoid photosensitizers, Gram-positive bacteria were inhibited after irradiation, but the activity against Gram-negative bacteria was limited. [29][30][31] In this study, we have obtained a low activity of chl-e6 and chl-e6H against a Gram-negative microorganism, and higher activity in a Gram-positive microorganism. Previous studies show that it is easier to inactivate Grampositive than Gram-negative bacteria, which can be explained by the electronic charges of the cell walls.…”
Section: Photodynamic Inactivation Of Microorganismsmentioning
confidence: 71%
“…In previous studies with porphyrinoid photosensitizers, Gram-positive bacteria were inhibited after irradiation, but the activity against Gram-negative bacteria was limited. [29][30][31] In this study, we have obtained a low activity of chl-e6 and chl-e6H against a Gram-negative microorganism, and higher activity in a Gram-positive microorganism. Previous studies show that it is easier to inactivate Grampositive than Gram-negative bacteria, which can be explained by the electronic charges of the cell walls.…”
Section: Photodynamic Inactivation Of Microorganismsmentioning
confidence: 71%
“…e group examined the effect of Ce6-mediated PDT on in vivo bacterial growth in a mouse model of skin infection with S. aureus, and the reduction in the intensity of bioluminescence was observed immediately aer PDT. Moreover, on the 5th day aer infection, the signal was almost undetectable in mice treated with Ce6-mediated PDT [61]. Dai et al reported that a new MBmediated APDT effectively treated C. albicans skin abrasion infections in mice [67].…”
Section: Recent In Vivo Studiesmentioning
confidence: 99%
“…e most efficient was the BF2 derivative [60]. Park et al demonstrated that chlorin Ce6-mediated PDT signi�cantly reduced the colony formation of S. aureus in a dose-dependent manner [61]. Based on these data, it is clear that APDT can effectively kill various microbial species growing in planktonic culture.…”
Section: Planktonic Culture Of Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation
“…PDI functions on the principle that the accumulation of a specific photosensitizer in the relevant tissue induces the generation of reactive oxygen species (ROS) when exposed to light of a specific wavelength. These ROS may kill bacteria and be the initial step in healing bacterial keratitis (13)(14)(15)(16)(17). The histopathology of bacterial infected mice indicates focal cellular infiltrates within the corneal stroma.…”
Section: Introductionmentioning
confidence: 99%